(untitled) (World Bulletin of Public Health, 2022)
The development of critical thinking in students is the basis for their development in society as professionals who own the skills of enterprising, inquisitive, creative, and able to correctly assess their behavior, have their own ideas, views, build and raise the foundation of our great future. Of course, the educational process is important in this field